2016
DOI: 10.1093/humrep/dew024
|View full text |Cite
|
Sign up to set email alerts
|

Natural cycle IVF reduces the risk of low birthweight infants compared with conventional stimulated IVF

Abstract: The study was supported by the following grants from the Eunice Kennedy Shriver National Institute of Child Health and Human Development, NICHD K12HD047018 (W.M.), NICHD K12HD001271 (L.A.K.). The authors have no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 19 publications
1
40
2
2
Order By: Relevance
“…Therefore, those in the AID group were more likely to use a natural cycle than those in the AIH group. Cycles with ovarian stimulation have been associated with a higher risk of LBW in infants than natural cycles (Kalra et al 2011;Mak et al 2016). There were 12 infants with LBW from ovarian stimulation cycles in the AIH group, while only 1 infant with LBW from natural cycle was born in the AID group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, those in the AID group were more likely to use a natural cycle than those in the AIH group. Cycles with ovarian stimulation have been associated with a higher risk of LBW in infants than natural cycles (Kalra et al 2011;Mak et al 2016). There were 12 infants with LBW from ovarian stimulation cycles in the AIH group, while only 1 infant with LBW from natural cycle was born in the AID group.…”
Section: Discussionmentioning
confidence: 99%
“…For children conceived by NC‐IVF, the incidence of SGA was analyzed only once, by Mak et al . They compared 190 singletons after NC‐IVF with 174 after c‐IVF.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found a significantly higher risk of low birthweight (LBW) after c‐IVF (risk ratio 1.95; 95% confidence interval [CI] 1.03‐3.67) compared with modified IVF/NC‐IVF therapy . Studies included in the review focused on birthweight as the main outcome and defined LBW as <2500 g, without taking into consideration exact gestational age . Using birthweight percentiles adjusts for gestational age and sex of the neonate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, fertility treatments that seek to balance optimal or physiologic reproductive function, surgically and/or medically, may result in lower incidence of multiple gestation and low birthweight. [18][19][20] Healthier birth outcomes for subfertile couples in the United States are not going to be achieved by simply expanding affordability and utilization of IVF. If the public has an interest in more equitable coverage for fertility treatment, it also has an interest in maximizing the public health outcomes related to fertility treatment.…”
mentioning
confidence: 99%